Hakikat Belajar dan Pembelajaran - Muhammad Ilham Qalit; Al-Qodri Mul Ihsan; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
An effective educational process involves three main components: learning, teaching, and learning. Learning is defined as the modification of behavior through experience, which includes changes in individual abilities. Teaching is an activity carried out by educators to transfer knowledge and skills to students, while learning is the interaction between educators and students in creating a conducive learning environment. This article discusses the definition, principles, and general procedures in learning, teaching, and learning. These principles include attention, motivation, activeness, direct involvement, repetition, reinforcement, and use of teaching materials. The learning procedure consists of introductory components, core activities, and closing. By understanding and applying these principles and procedures, it is hoped that the learning process can take place optimally and produce positive changes in students.